Habluminallah and Habluminannas : Perilaku Charity antara Muslim Nahdlatul Ulama And Muhammadiyah - Muhammad Abdul Rohman Rohman; Dendy Herdianto; Nurita Afridiana (Asyafina Akademik Press, 2022)
This study aims to determine the effect of the level of religiosity with charity between NU and Muhammadiyah organizations. This study is also to find out the factors that significantly affect charity between NU and Muhammadiyah organizations. This study uses IFLS data in 2014 with the ordinary least square method. The results of this study indicate that the level of religiosity factor has a positive relationship to the level of charity in the Muslim estimation model, except for Muhammadiyah Muslims, a significant positive relationship occurs in the second model while the others have no significant effect on charity behavior.